A REVIEW ON RHEUMATOID ARTHRITIS - Sanjay, Bhandari Singh; Kunal, Khurana; Ankur, Balyan; Kapil, Negi Dev; Prasad, Kabra Mahaveer (Asian Journal of Pharmaceutical Research and Development, 2013)
RA is chronic, autoimmune, inflammatory disease that affects the skin, blood vessels, CVS, lungs and muscles but principally attacks the joints to destruction of the articular cartilage and ankylosis of the joints causing aching, pain, swelling and stiffness.The disease can affect at any age but old persons are mainly affected. There is no specific cause of RA but some factor may play important role in the progress of RA. A blood antibody called "rheumatoid factor" can be found in 80% of patients, is the principle factor for diagnosis RA. The drugs most commonly used in the therapy of RA are the disease modifying antirheumatoid drugs (DMARDS) and the NSAIDS.